REGULATORY IMPACT ASSESSMENT (RIA) SEBAGAI APLIKASI RASIONAL EKONOMI DALAM MENILAI KELAYAKAN TATANIAGA TEMBAKAU DI MADURA - Bondan Satriawan (Trunojoyo University of Madura, 2009)
This study assesses the feasibility of local or municipal policy in terms of regulation from economics rationale point of view. To do so, this study makes use the methodology of soft or mini RIA (Regulatory Impact Assessment) as well as the linear ralationship between competition and performance approach. Focus of assessment of this study is the regulations that regulate tobacco's industry in Madura.There are two local or municipal regulations in Madura as the basic for regulating tobacco's industry, they are, first, Sumenep's regional law No. 6/2002 about Regulation and Permits' fee of tobacco business. Second is Pamekasan's regional law No. 2/2008 about tobacco's business regulation.The assessment concludes that these regulations have strong economics rationale behind them, is justified by public interest, relatively low cost for business and government, have no negative effects on the basic freedom of civil society. From economics point of view, It can be said that the regulations are low cost and low risk.